2015
DOI: 10.1071/cp13406
|View full text |Cite
|
Sign up to set email alerts
|

Use of functional traits to identify Australian forage grasses, legumes and shrubs for domestication and use in pastoral areas under a changing climate

Abstract: Abstract. Considerable uncertainty exists about future climatic predictions but there is little doubt among experts that the future will be warmer. Climate change and the associated elevation in atmospheric CO 2 level and temperatures will provide novel challenges and potential opportunities for cultivated plant species. Plant breeding and domestication can contribute to improvements in both yield and quality of native grasses, legumes and forage shrubs. This review explores the use of functional traits to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 120 publications
(135 reference statements)
0
9
0
Order By: Relevance
“…This study indicates that the water consumption and deficit of deep soil increased with increasing alfalfa planting years, especially in the four-and seven-year-old alfalfa pastures. SWS is a critical indicator for the planting and production of alfalfa pastures in pastoral areas [21]. In this study, SWS of the four-and seven-year-old alfalfa pastures decreased with increasing soil depth within the 0-350 cm range.…”
Section: Discussionmentioning
confidence: 59%
“…This study indicates that the water consumption and deficit of deep soil increased with increasing alfalfa planting years, especially in the four-and seven-year-old alfalfa pastures. SWS is a critical indicator for the planting and production of alfalfa pastures in pastoral areas [21]. In this study, SWS of the four-and seven-year-old alfalfa pastures decreased with increasing soil depth within the 0-350 cm range.…”
Section: Discussionmentioning
confidence: 59%
“…When plants reached maturity stage which lasted from the end of August till the beginning of October, they were harvested and data were collected from ten tagged plants per experimental plot. Twenty two growth parameters were monitored in total and divided in five groups based on the functionality of the traits (adapted from Mitchell et al 2015;Perez-Harguindeguy et al, 2013;Chen et al, 2012). All the agronomic parameters are listed in Table 8.…”
Section: Data Collectionmentioning
confidence: 99%
“…Since there are no references for the natural occurrence of S. bigelovii in the region and no bred material is available for planting, wild collections of the halophytic species are introduced and undergo the domestication process. Germplasm characterization is needed in order to identify the functional traits of the best performing genotypes in terms of seed and biomass yield with promising breeding value (Mitchell et al, 2015;de Galarreta and Alvarez, 2001;Gepts, 2004). Through selection of plants for desirable traits, agronomic parameters are identified that ultimately improve crop productivity (Brown et al, 2014;Ruan et al, 2010;Zerai et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous legumes were originally endemic to native pasture in semiarid ecosystems around the world (Mitchell et al, 2015;Ydoyaga-Santana et al, 2011). Forage and seeds of these plants can contribute as feed to native fauna, forage to domesticated ruminants, as well as N and organic matter to native soils and plants unable to fix atmospheric N (Muir et al, 2005;Noah et al, 2012).…”
Section: Introductionmentioning
confidence: 99%